Turning nursing students’ mistakes into resources for learning in simulation-based training: facilitators’ assumptions about providing feedback in debriefing - Wenche Lervik; Mads Solberg; Astrid Camilla Wiig; Helen Berg (BMC Medical Education)
Abstract Background The aim of this study was to investigate how facilitators approach and use nursing students’ mistakes in simulation-based training as learning resources in the simulation debriefing phase. Facilitators are responsible for raising students’ awareness of their performances during the debriefing and facilitating reflections on their performances, including satisfactory behaviours and performance gaps. Research on facilitators’ work during debriefing has highlighted various challenges, such as providing a safe and constructive climate among novice students while simultaneously teaching them the correct procedures, methods, and knowledge of caring practices to become professional nurses. There is a lack of research on how facilitators approach, handle, and use students’ mistakes as a learning resource. Thus, this study investigated facilitators’ assumptions about providing feedback to nursing students when they made mistakes during simulation-based training Method Individual semi-structured interviews were conducted with nine experienced facilitators from three universities in Norway. Data were analyzed following the principles of thematic analysis (TA). Results Facilitators made varying assumptions about the simulations and debriefings as learning processes. These differences were evident in their accounts of how feedback was provided to students when they made mistakes during the simulation-based training. Conclusion Facilitators’ statements about their practices reflect assumptions about how they make simulation activities a resource for meaningful learning, including how to use students’ mistakes as learning opportunities during debriefing discussions. Consequently, these assumptions regarding learning provide valuable insights into the ambiguous and complex praxis of using simulation-based training as a professional educational tool.